A Study of Axial Impact of Composite Rods Using SPH Approach - K.Y. Lam; Y.G. Shen; S.W. Gong (Shock and Vibration)
A computational simulation of axial impact between composite rods is presented in this paper. The smoothed particle hydrodynamic (SPH) method is coded and implemented for this study, in which the property and strength for different materials are included. The SPH formulation for impact between rods as well as its computatinal procedure is also expounded. The present approach is used to study impact between composites rods parametrically. The effects of material properties and configurations of composite rod on impact response are then examined in detail. In addition, the present SPH results are compared with those from theoretical analysis.